Optimizing Particle Density for Accurate Wave Simulation: A Comparative Study of Non-Breaking and Breaking Wave Conditions - Thi-Quynh Nguyen; Kyong-Hwan Kwon; Chang-Wook Park; Kwang-Ho Lee (Journal of Marine Science and Engineering)
This study investigates the optimal particle density for accurate wave simulation in non-breaking and breaking wave conditions using Smoothed Particle Hydrodynamics (SPH). Simulations were conducted using various particle densities, or particles per wavelength, to evaluate their impact on simulation accuracy and computational efficiency. In tests involving regular, non-breaking waves, particle densities in the range of np per L = 560 to 800 were found to provide satisfactory accuracy and computational efficiency. Increasing the particle density beyond np per L = 800 for more complex setups involving breaking waves did not significantly improve accuracy but resulted in much higher computational costs. Overall, the range of np per L = 560 to 800 offers the best balance between accuracy and efficiency, making it a practical choice for simulations with limited resources. This study underscores the trade-offs between accuracy and computational demand, providing guidance on the selection of particle density for various wave simulation scenarios.